Competition in the Globalization Era and his Effects on Geoeconomics - Palomo Garrido, Aleksandro (Geopolítica(s). Revista de estudios sobre espacio y poder, 2017)
This paper sets out to explain the increasing competition among the different economic actors of the international system —and its corresponding geoeconomic effects— brought about by globalization processes. The expansion of global commerce fostered a grueling race where actors competed for gaining greater shares in the global market. The paper argues that as the market was booming, there was room for anyone wishing to participate. But in the wake of economic crises, opportunities narrowed down and the competition for keeping market shares rocketed. Simultaneously, opportunities for accessing raw materials diminished. In short, the increasing competition promoted by globalizing trends engendered pressures that, in turn, led to strained relations among the different actors competing for a share in the global market.
Keywords: globalization; competition; emerging powers; trade expansion; natural resources